Bahasa Inggris - Purwanti Purwanti; Muhammad Syaipul Hayat; Endah Rita Sulistya Dewi (Jurnal Penelitian Pendidikan IPA, 2024)
21st century education demands innovation in learning to develop students' creative thinking skills.  This study aims to measure the effect of implementing STEAM-SDGs-based science learning on the concept of energy on students' creative thinking skills. The research method used a quasi-experimental method with a one-group pretest-posttest design. The subjects of the study were 32 students of grade VIII of SMP Negeri 1 Jumo, Temanggung Regency. Data collection was carried out using a creative thinking skills test instrument and the research data were analyzed using the rasch model. The results showed a significant increase in students' creative thinking skills, with an average pretest score of 35.83 and a posttest score of 82.32. Welch's t-test showed a significant difference between the pretest and posttest (t = -6.31, df = 55, and prob = 0.001, p <0.05). The greatest increase occurred in the fluency, flexibility, and elaboration indicators, while the originality indicator experienced a lower increase. STEAM-SDGs integration has proven effective in improving students' creative thinking skills, with the highest indicator in flexibility (90.24) and the lowest in originality (69.93). This study suggests that combining STEAM with global sustainability issues such as the SDGs can prepare students to face 21st century challenges and increase their awareness of environmental and sustainability issues.